Incompressibility of the solid matrix of articular cartilage under high hydrostatic pressures - Bachrach, Nathaniel M.; Mow, Van C.; Guilak, Farshid (Journal of biomechanics, 1998)
The objective of this study was to test the hypothesis that the organic solid matrix of articular cartilage is incompressible under physiological levels of pressure. Due to its anisotropic swelling behavior, an anisotropic version of the biphasic theory was used to predict the deformation and internal stress fields. This theory predicts that, under hydrostatic loading of cartilage via a pressurized external fluid, a state of uniform hydrostatic fluid pressure exists within the tissue regardless of the anisotropic nature of the solid matrix. The theory also predicts that if the solid matrix is intrinsically incompressible, the tissue will not deform under hydrostatic loading conditions. This prediction, i.e., no deformation, was experimentally tested by subjecting specimens of normal bovine articular cartilage to hydrostatic pressures. A new high pressure hydrostatic loading chamber was designed and built for this purpose. It was found that normal bovine articular cartilage, when subject to hydrostatic pressures up to 12 MPa, does not deform measurably. This experimental finding supports one of the fundamental assumptions of the biphasic theory for cartilage, i.e., the organic solid matrix of the tissue is intrinsically incompressible when loaded within the normal physiologic range of pressures. Hydrostatic loading has often been used in cartilage explant cultures for tissue metabolism studies. The findings of this study provides an accurate method to calculate the states of stress acting on the fluid and solid phases of the tissue in these hydrostatically loaded explant culture experiments, and suggest that tissue deformation will be minimal under pure hydrostatic pressurization.